Growth Dynamics of Major Mangrove Species in the Sundarbans Reserve Forest of Bangladesh - Siddqui, ASM Helal; Islam, Md. Akramul (International Journal of Scientific Research in Biological Sciences, 2021)
To conduct the present study, data was collected from 33 Permanent Sample Plots with a view to observing the growth dynamics of important mangrove species with a multistage sampling technique in the Sundarbans Reserved Forest (SRF), Bangladesh. The salinity of the soil varies from 5 to 28 ppt and PH ranges from 5.0 to 6.0. There were 25970 ha-1 of seedlings in the LSWZ (>5 ppt), 32212 ha-1 in the MSWZ (5-18 ppt), and 26424 ha-1 in the SSWZ (>18 ppt). The chronology of the total number of seedlings in each salinity zone were 43%, 24%, and 33% respectively. Total numbers of regeneration for H fomes 9303, 5970 and 4818; E agallocha 7273, 12970, 3091; for C decandra 2303, 636, 11242; for X moluccensis 879, 909,233; for B sexangula 2788, 1303, 152; for S apetala 333, 1273, 0; for A officinalis 697, 636, 30; for C ramiflora 758, 30,0; for A corniculatum 242, 30, 4576; for R apiculata 121, 606,0; for A cucullata 394, 394, 182; for P paludosa 485, 0,0 and for N fruiticans 485, 455,0 in less, moderate and strong salinity zones consecutively. Total regeneration percentage with average annual increase of growth (DBH, cm and Height, m) of each species of H fomes 27.5%, 0.025 and 0.020; E agallocha 7.0%, 0.023 and 0.012; C decandra 39.2%, .033 and 0.034; B sexangula 13.6%, 0.156 and 0.055; X mekongensis 3.1%, 0.029 and 0.028; A officinalis 4.6%, 0.024 and 0.053; S apetala 0.8%, 0.146 and 0.348; A corniculatum 0.6%, 0.019 and 0.156 in different saline zone of Sundarbans.